Seismostratigraphy of the Ceará Plateau: Clues to Decipher the Cenozoic Evolution of Brazilian Equatorial Margin - Jovane, Luigi; Figueiredo, Jorge J. P.; Alves, Daniel P. V.; Iacopini, David; Giorgioni, Martino; Vannucchi, Paola; Moura, Denise S.; Bezerra, Francisco H. R.; Vital, Helenice; Rios, Isabella L. A.; Molina, Eder C. (Frontiers in Earth Science, 2016)
The Ceará Plateau offshore Fortaleza holds some particular characteristics when compared to the other seamounts of the Brazilian Equatorial Margin (BEM). Not only it is the largest and the closest to the continent, it is also located at the boundary between the continental and the oceanic crusts, while all the others seamounts along the BEM are located on oceanic crust. Seismic imaging of the Ceará Plateau shows a “disorganized” interior, probably of volcanic origin, overlain by a series of horizontal seismic reflectors that can be interpreted as pelagic/hemipelagic sediments. As large uncertainties exist about the age of the initial formation of this seamount, three scenarios must be considered. If the age of the volcanic edifice is Coniacian (1), then the overlying pelagic/hemipelagic sedimentary succession can include an almost continuous record of the last ~90 Ma at the Equatorial Atlantic Ocean. In the case that the volcanic edifice is Eocene in age (2), the sedimentary sequence would still encompass the upper Paleogene and all the Neogene. There is also the possibility that the volcanic edifice was built during multiple magmatic events (3). In this case, it is likely that the sediments are interfingered with volcanic rocks at the edge of the structure. Although the age estimation (between Coniacian and Eocene) has an uncertainty of more than 40 Myr, the current interpretation is that it developed initially as a volcanic edifice, formed by a series of magmatic events that occurred between the Santonian and the Eocene. Since then, the topography has been leveled by pelagic/hemipelagic sedimentation. Whichever was the initial age, a continuous and constant sequence of sediments deposited onto the Ceará Plateau, at the same latitude, and thus under the same oceanographic conditions, for the last several tens of million years. This represents a unique opportunity to record a long-term history of the Atlantic Equatorial Margin.